A comparison of the effectiveness of Alanine amino transferase enzyme (ALT) between the hypothermia and the normal state in the liver and blood of Syrian hamsters - فاضل, هيام; سعد, سوسن; عفيصه, هاجر (Latakia University Journal -Biological Sciences Series, 2022)
The effect of hypothermia on the enzymatic activity of the alanine aminotransferase enzyme ALT was studied on 32 animals of Syrian hamsters of average 7-9 months and weights between (90-120) g under heat condition (25 ° C) and suitable lighting (12:12), and left for acclimatization. For a period of at least 9 weeks before the start of the experiment. Blood samples were obtained from the heart, then centrifuged, hamster livers were excised, weighing 1.5-1 g, diluted with sucrose to a volume of 9 ml, extracts were porous and then diluted with cold distilled water. 4 test tubes (2 controls and 2 experiments) were prepared and poured into a water bath at temperatures: 10- 20 -25-30-37 for 60 minutes. To the sample of the experiment was added 0.5 ml of 4,2-dinitrophenylhydrazine solution, to the control dinitrophenylhydrazine and 0.5 ml of the substrate. After leaving for 20 minutes, a solution of NaOH (0.4 N) was added to all samples. The chromatic intensity was measured using a spectrophotometer. The results of this study showed that the activity of the ALT enzyme in the liver in the normal state and hypothermia is directly proportional to the rise of temperature, reaching its highest at 37° C compared to other values ​​in the lower temperatures, but the enzymatic activity during hypothermia at 37° C was lower than its level in the normal state, while at 25 and 30 degrees Celsius, the efficiency of hypothermia was higher than the normal state, which indicates the resistance of the hamster's body to forced hypothermia as it is one of the animals that undergoes hibernation. The efficiency of ALT in serum decreased significantly compared to its effectiveness in the liver, and this indicates decrease in the level of this enzyme in the serum. The results of the statistical analysis showed that there was no significant differences for the effect of temperatures 30-25 on enzymatic activity, while there was significant differences between the averages of activity at degrees 37-20-15 between them in the normal state in the liver and blood, and in the case of hypothermia in the liver only. While it was recorded in the blood in the case of thermal decline that there was significant differences for the effect of temperatures 25-15 on the activity of the enzyme, as well as significant differences at the 30 and 37 degrees compared to the other values.